REVIEW OF THE MONOGRAPH «FORMATION OF STRATEGY IN ANTI-CRISIS MANAGEMENT OF OPERATIONAL ACTIVITY OF INDUSTRIAL ENTERPRISES», PREPARED BY SHVETS YU.O. - Marchenko, V.M. (Фінансові стратегії інноваційного розвитку економіки, 2021)
REVIEW OF THE MONOGRAPH «FORMATION OF STRATEGY IN ANTI-CRISIS MANAGEMENT OF OPERATIONAL ACTIVITY OF INDUSTRIAL ENTERPRISES», PREPARED BY SHVETS YU.O.